2019
DOI: 10.1002/ijc.32010
|View full text |Cite
|
Sign up to set email alerts
|

Selective BTK inhibition improves bendamustine therapy response and normalizes immune effector functions in chronic lymphocytic leukemia

Abstract: The Bruton's tyrosine kinase (BTK) inhibitor ibrutinib has been shown to be highly effective in patients with chronic lymphocytic leukemia (CLL) and is approved for CLL treatment. Unfortunately, resistance and intolerance to ibrutinib has been observed in several studies, opening the door for more specific BTK inhibitors. CC‐292 (spebrutinib) is a BTK inhibitor with increased specificity for BTK and less inhibition of other kinases. Our in vitro studies showed that CC‐292 potently inhibited B‐cell receptor sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In vitro CLL proliferation assay CLL primary cells (10 7 cells) were labeled with 0.5 µM carboxy uoresceinsuccinimidyl ester (CFSE; Life Technologies) as reported previously [13,14]. Brie y, 10 5 cells/200 μL were cultured for 6 days in an enriched RPMI-1640 supplemented with 15 ng/mL recombinant human IL-15 (R&D systems, Minneapolis, MN) to sustain survival and with 0.2 μM CpG DNA TLR-9 ligand (ODN-2006; Invivogen, San Diego, CA) to induce cell proliferation [15].…”
Section: Analysis Of Cytotoxicity and Active Metabolic Activity (Mtt)mentioning
confidence: 99%
“…In vitro CLL proliferation assay CLL primary cells (10 7 cells) were labeled with 0.5 µM carboxy uoresceinsuccinimidyl ester (CFSE; Life Technologies) as reported previously [13,14]. Brie y, 10 5 cells/200 μL were cultured for 6 days in an enriched RPMI-1640 supplemented with 15 ng/mL recombinant human IL-15 (R&D systems, Minneapolis, MN) to sustain survival and with 0.2 μM CpG DNA TLR-9 ligand (ODN-2006; Invivogen, San Diego, CA) to induce cell proliferation [15].…”
Section: Analysis Of Cytotoxicity and Active Metabolic Activity (Mtt)mentioning
confidence: 99%
“…The resultant clear solution was further stirred overnight. After removal of the white precipitate by filtration, the filtrate was evaporated to dryness under reduced pressure, and the residue was purified by flash chromatography to afford compound 7 (1.8 g, 64.5%); 1…”
Section: Preparation Of Benzyl 4-(5-(benzyl(2-((4-(5-(dibenzylamino)-mentioning
confidence: 99%
“…It features an active nitrogen mustard moiety (mechlorethamine unit) together with a benzimidazole ring and a butanoic acid residue. [1][2][3][4] Its mechlorethamine moiety Bendamustine deschloro dimer, a potential impurity of bendamustine hydrochloride, has been efficiently synthesized from compound 1 in nine steps which involve two key intermediate compounds 4 and 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zanubrutinib was efficacious in clinical trials of patients with MCL and CLL/SLL, was recently FDA approved for MCL treatment (32), and is being investigated in patients with WM (33)(34)(35)(36). Another BTK inhibitor, spebrutinib (CC-292), impaired CLL cell proliferation and improved control of CLL progression when given concurrent with bendamustine in preclinical models (37). However, in a phase 1 study, spebrutinib monotherapy had a shorter duration of response than those reported for ibrutinib or acalabrutinib, although it was well tolerated (38)(39)(40).…”
Section: Introduction To Bruton Tyrosine Kinase Inhibitorsmentioning
confidence: 99%